NUMERICAL ANALYSIS OF MATHEMATICAL MODELS OF THE FACTUAL CONTRIBUTION DISTRIBUTION IN ASYMMETRY AND DEVIATION OF VOLTAGE AT THE COMMON COUPLING POINTS OF ENERGY SUPPLY SYSTEMS - Yu.L. Sayenko (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. Perform numerical analysis of the distribution of the factual contributions of line sources of distortion in the voltage distortion at the point of common coupling, based on the principles of superposition and exclusions. Methodology. Numerical analysis was performed on the results of the simulation steady state operation of power supply system of seven electricity consumers. Results. Mathematical model for determining the factual contribution of line sources of distortion in the voltage distortion at the point of common coupling, based on the principles of superposition and exclusions, are equivalent. To assess the degree of participation of each source of distortion in the voltage distortion at the point of common coupling and distribution of financial compensation to the injured party by all sources of distortion developed a one-dimensional criteria based on the scalar product of vectors. Not accounting group sources of distortion, which belong to the subject of the energy market, to determine their total factual contribution as the residual of the factual contribution between all sources of distortion. Originality. Simulation mode power supply system was carried out in the phase components space, taking into account the distributed characteristics of distortion sources. Practical value. The results of research can be used to develop methods and tools for distributed measurement and analytical systems assessment of the power quality.